Assessment of Prospective Preventive Therapies for Chronic Wasting Disease in Mule Deer - Wolfe, Lisa L. (J Wildl Dis, 2012)
We compared prion infection rates among mule deer (Odocoileus hemionus) receiving pentosan polysulfate, tannic acid, tetracycline HCl, or no treatment 14 days before to 14 days after (dpi) oral inoculation with tonsil tissue homogenate. All deer were infected, but the rapid disease course (230–603 dpi) suggested our challenge was overwhelming.